Fundamentals of metal-matrix composites - Suresh, S.; Mortensen, A.; Needleman, A. (Butterworth-Heinemann, 1993)
Focuses on the following areas of metal composites: processing, microstructure and characterization, mechanics and micromechanics of deformation, mechanics and micromechanics of damage and fracture, and practical applications.
Keywords: Metallic composites.; elektronické knihy; electronic books